CORPORATE DISTRIBUTIONS AS INCOME TO STOCKHOLDERS. - Kerrigan, Harry D. (The Accounting Review, 1938)
Distributions by corporations differ in amount, frequency, and mediums of payment, but all are popularly known as dividends. Some dividends are stated amounts paid at stipulated intervals; such is the case of dividends on so-called preferred stock. Other dividends are unstated before actual declaration by the directors' resolution, both the amount and the frequency of the dividend being left to the discretion of directors in accordance with the contractual terms of the shares owned by the stockholders. This is the usual arrangement under which dividends on common stock are paid. Variation also exists in the medium of dividend payment. The most important medium used is corporate assets, cash being by far the leading specific asset used. Another form is the distributing corporation's obligations, scrip or note payable being the common forms. The third principal medium is un-issued capital stock. Adoption the requisite of realization has introduced another difficulty; it raises the issue of what constitutes realization. Ordinary dividends paid in cash constitute income upon receipt if it be admitted that any realized money gain is income. Money income is the closest practical thing to real income evidenced by consumable commodities and services. This is the chief virtue of income received in cash. However, the receipt of money's worth has come to be recognized as the equivalent of money because the bulk of business claims are not actually liquidated in cash. Thus cash dividends are commonly paid by check which are taken up as income upon receipt.